2017
DOI: 10.1080/09593330.2017.1371251
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temporal variability of excess sludge characteristics on the effects obtained in the process of its ultrasonic disintegration

Abstract: This paper aimed to indicate the characteristics of excess sludge, which have the greatest impact on the effects obtained during its ultrasonic disintegration (UD). The direct and technological effects observed after sludge disintegration and anaerobic digestion (AD) depend on the factors affecting the quality of its matrix and simply on the parameters of a disintegrator. Sludge samples originate from a Central Waste Water Treatment Plant in Gliwice, and were collected after mechanical thickening by a monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, it is necessary to reduce the many-hours-long sample shaking procedure and/or replace it with another process that would enable results similar to those obtained with the conventional method to be achieved. The most promising and beneficial method seems to be ultrasonication (sonication), which is based on the cavitation phenomenon [ 5 , 21 , 22 ]. It has been shown that the cavitational effect generated by ultrasound can fragment particles and cause microcracks, which in turn accelerate various physicochemical processes, i.a., digestion, dissolution, extraction, or leaching [ 5 , 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to reduce the many-hours-long sample shaking procedure and/or replace it with another process that would enable results similar to those obtained with the conventional method to be achieved. The most promising and beneficial method seems to be ultrasonication (sonication), which is based on the cavitation phenomenon [ 5 , 21 , 22 ]. It has been shown that the cavitational effect generated by ultrasound can fragment particles and cause microcracks, which in turn accelerate various physicochemical processes, i.a., digestion, dissolution, extraction, or leaching [ 5 , 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%